Pemanfaatan Internet oleh Penyuluh Pertanian - Eksanika, Putri; Riyanto, Sutisna (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
The development of information technology and communication is increasingly perceived by the public, one of them internet. Agricultural extension worker as the spearhead of agricultural development has an important role in assisting the development of agriculture. Internet as a medium that stores a variety of information on agriculture and as a medium of communication can be used to support the agricultural extension activities. The purpose of this study is to analyze the understanding of agricultural extension worker to the internet, analyze the behavior of internet usage by agricultural extension worker, and analyze the utilization of the internet by agricultural extension worker. This study was conducted using a quantitative approach that is supported by qualitative data. Quantitative data collected using questionnaires to 16 people from the agricultural extension worker of BP3K Dramaga and 22 people from the agricultural extension worker of BP3K Cibungbulang, the qualitative data obtained through interviews and observations. Obtained data analyzed using descriptive analysis and correlation tests. The results showed that agricultural extensions worker is sufficient used the internet to support in agricultural extension activities.Keywords: information technology, communication, agricultural extensionÂ ——————————–ABSTRAKPerkembangan teknologi informasi dan komunikasi semakin dirasakan oleh masyarakat, salah satunya internet. Penyuluh pertanian sebagai ujung tombak pembangunan pertanian memiliki peran penting dalam membantu perkembangan pertanian. Internet sebagai media yang menyimpan berbagai informasi tentang pertanian dan sebagai media komunikasi dapat digunakan untuk mendukung kegiatan penyuluhan pertanian. Tujuan dari penelitian ini adalah untuk menganalisis pemahaman penyuluh pertanian pada internet, menganalisis perilaku penggunaan internet oleh penyuluh pertanian, dan menganalisis pemanfaatan internet oleh penyuluh pertanian. Penelitian ini dilakukan dengan menggunakan pendekatan kuantitatif yang didukung oleh data kualitatif. Data kuantitatif dikumpulkan dengan menggunakan kuesioner untuk 16 orang dari penyuluh pertanian dari BP3K Dramaga dan 22 orang dari penyuluh pertanian dari BP3K Cibungbulang, data kualitatif diperoleh melalui wawancara dan observasi. Data yang diperoleh dianalisis menggunakan analisis deskriptif dan uji korelasi. Hasil penelitian menunjukkan bahwa penyuluh pertanian telah cukup menggunakan internet untuk mendukung kegiatan penyuluhan pertanian.Kata kunci: teknologi informasi, komunikasi, penyuluhan pertanian